Enhancing students' reading comprehension achievement using patner reading strategy - Ratna Nery (Relawan Jurnal Indonesia, 2020)
This research aimed to investigate whether the students who were taught using Partner Reading Strategy had better reading comprehension achievement than those who were not. The method used was quasi-experimental. The sample of this study was 70 tenth graders involved experimental group (class X MIPA 2) and control group (class X MIPA 3). Each group consisted of 35 students. The written test in the form of multiplechoice was administered to get data collection. Before giving the test, the test was tried out to non-samples students of the eighth-grade students of SMA Negeri 4 Kayuagung class X MIPA 1 to check the validity and reliability of the test. The data were analyzed using t-test. The result of the t-test was significant at p<0.05 with df = 68, the critical value of ttable = 1.995. Since the value of tobtained (9.304) was higher than the critical value of ttable = (1.995), Ho was rejected and Ha was accepted. It means that the students who were taught using Partner Reading Strategy had comprehension in reading that made their reading comprehension achievement improve better and that those who were not.